Recombinant DNA: Genes and genomes-a short course - Watson, James D.; Watson, James D.; Caudy, Amy A.; Myers, Richard M.; Witkowski, Jan A. (New York, W H Freeman and Company, 2007)
With an reliable, accessible, and intriguing introduction to modern, genome-centered biology from its foremost practitioners, Recombinant DNA: Genes and Genomes explores core concepts in molecular biology through the most relevant and exciting examples of current research and landmark experiments that redefined our understanding of DNA.
Index 461-474p.
Keywords: DNA; Recombinant; Recombinant DNA-Research